The role of local pigs for economic and socio-cultural in East Flores District, East Nusa Tenggara, Indonesia - Arkadius Suban Keray; Rini Widiati; Tri Anggraeni Kusumastuti (Society for Indonesian Biodiversity, 2024)
Abstract. Keray AS, Widiati R, Kusumastuti TA. 2024. The role of local pigs for economic and socio-cultural in East Flores District, East Nusa Tenggara, Indonesia. Biodiversitas 25: 214-222. This study was conducted to identify the cultural activities related to swine rearing in East Flores District and analyze the decision making in choosing the types of rearing practice. Based on the survey using questionnaires from 120 pig farmers, which was conducted purposive, were those who had at least three sows for breeding, fattening with five heads of pigs, and combined with sows and sires. To identify the role of local pigs, as many as 3 informants consist of traditional leaders, farmers, and Agriculture Extension Officers, and analyzed by multinomial logistic regression model. The results showed that the traditional rituals that required the sacrifice of pigs included the ceremonies marking the start of building residential and traditional community buildings and dowry (belis) presentation in a wedding ceremony. The decision-making in choosing the rearing practice was influenced by pig ownership, care system (P<0.01), and income (P<0.05). Farmers who have small scale will choose extensive and fattening systems to reduce feed costs. Those practicing breeding are still maintaining local breeds because traditional rituals require it. Further efforts are needed to increase the populations of local breeds as well as cross-bred pigs to maintain the ceremonies in traditional rituals and income generation.